Encroachment of Agricultural Land and Urban Development Issues; A Case of Bagdula, Pyuthan - Adhikari, Samiksha; Yogi, Manisha (Journal of Advanced College of Engineering and Management, 2025)
Land use pattern is changing day by day in Global context to national context, the major cause of change is human and their interaction with natural environment. Evidence shows agricultural land abandonment is a global land change. Populations grows and increase in agricultural demand that also rise to demand in housing land which causes for destroy of existing agricultural land in unplanned haphazard way. In scenario of Nepal a new mode of political, social and economic transformation is promoting the haphazard encroachment of agricultural land. Case study of Bagdula, Pyuthan is done to analyze the root cause and problems of change in land use pattern, also to predict the future scenario of Bagdula area through the survey data. The small neighborhood of Bagdula has been selected for the study of changing land use of the area. This area is a part of Bagdula bazaar. This article looks upon encroaching the agricultural land of surrounding, with the ongoing development and extension various consequences are emerging. Random field survey has been done for the data collection. Twenty houses are selected from the neighborhood as per the ease for surveyor due to pandemic. All the respondents are the owner of the buildings and most of the people are involved in business activities. Satellite images are also used for the data analysis which supports the data collected from the survy. This study helps us to understand the changing land use pattern of different part of Nepal. Root cause and problems of changing land use can be understood during this study. Also to predict the future scenario of this settlement this study can be beneficial.